The Influence of Islamic Marketing Ethics and Sharia Service Quality on Customer Trust: A Case Study from BMT Al-Hidayah - Nurmila sari, Desi; Marjan; Gunawan, M. Indra (Li Falah: Journal of Islamic Economics and Business, 2025)
The purpose of this study is to examine the influence of Islamic Marketing Ethics and Islamic Quality Service on Customer Trust in an Islamic microfinance institution. This research employed a quantitative approach and was conducted from April to September 2025. The study involved 98 customers of BMT Al-Hidayah using a simple random sampling technique. Data were collected through questionnaires and analyzed using simple linear regression and multiple regression methods. The findings revealed that Islamic Marketing Ethics significantly influenced customer trust with an R² value of 0.280, while Islamic Quality Service had a significant influence with an R² value of 0.288. The combined influence of both variables on customer trust resulted in an R² value of 0.368. These results indicate that trust in Islamic financial services is driven by the institution’s adherence to ethical marketing and the delivery of Sharia-compliant service quality. Future studies are recommended to explore additional factors such as religiosity, customer experience, or institutional image using mixed method approaches for a more comprehensive understanding of trust development.